Invariance of the magnetic behavior and AMI in ferromagnetic biphase films with distinct non-magnetic metallic spacers - Silva, E. F. (2020)
We investigate the quasi-static magnetic, magnetotransport, and dynamic magnetic properties in ferromagnetic biphase films with distinct non-magnetic metallic spacer layers. We observe that the nature of the non-magnetic metallic spacer material does not have significant influence on the overall biphase magnetic behavior, and, consequently, on the magnetotransport and dynamic magnetic responses. We focus on the magnetoimpedance effect and verify that the films present asymmetric magnetoimpedance effect. Moreover, we explore the possibility of tuning the linear region of the magnetoimpedance curves around zero magnetic field by varying the probe current frequency in order to achieve higher sensitivity values. The invariance of the magnetic behavior and the asymmetric magnetoimpedance effect in ferromagnetic biphase films with distinct non-magnetic metallic spacers place them as promising candidates for probe element and open possibilities to the development of lower-cost high sensitivity linear magnetic field sensor devices